Оцінка стійкості екосистем на основі аналізу рольових трофічних мереж - Rudenko, S. S.; Bujdigan, O. Ya. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The theoretical ground and different approaches to the determination and estimation of the sustainability of ecological systems are presented. Innovative technology of the determination of sustainability of different types (resistant and resilient) of pastoral ecosystems by the estimated figures of role food webs. On the base of the complex of the developed figures of role food, webs the state of 31 pastoral ecosystems in Chernivtsy Region is estimated.